Kecemasan Berbahasa dalam Arabic Club: Studi Kasus pada SMA IT Daarul Qur’an Mulia Bogor - Mauludi Rizki, Muhamad; Alawiyah, N. Lalah; Edidarmo, Toto (Kopertais Wilayah I DKI Jakarta dan Banten, 2025)
This study aims to analyze the implementation of Arabic Club activities, the level of Arabic language anxiety experienced by students, and the contributing factors to that anxiety at Daarul Qur’an Mulia Islamic Senior High School, Bogor. Although the Arabic Club is designed to enhance Arabic language skills, some students still exhibit symptoms of anxiety, such as shyness, fear of making mistakes, and lack of self-confidence. Employing a qualitative approach with a case study method, data were collected through observation, interviews, FLCAS questionnaire, and documentation. The subjects involved 45 Arabic Club members, the club advisor, and Arabic language teachers. The findings indicate that the club is held weekly using interactive methods such as question-and-answer sessions, text reading, and educational games with digital media. However, FLCAS results show that most students experience moderate anxiety (75.56%), while the rest show high anxiety (24.44%), with no students reporting low anxiety. The highest anxiety level is associated with Fear of Negative Evaluation, followed by Communication Apprehension and Test Anxiety. Internal factors such as lack of self-confidence, limited vocabulary, and insufficient speaking practice are the primary causes of anxiety, while external factors like pressure when speaking in front of teachers also play a role. Strategies used by students and teachers to manage anxiety include independent practice, thorough preparation, gradual exposure, and creating a supportive learning environment. The study concludes that reducing language anxiety requires the integration of affective approaches and communicative teaching techniques tailored to students’ abilities, and the results are expected to serve as a reference for the development of a more effective and student-friendly Arabic Club.